Strengthening Religious Moderation Through PAI Learning at Sma Negeri 3 Blitar - Istikhori, Istikhori; Sahroni, Dadang; Yurna, Yurna; Hilman, Cecep (West Science Interdisciplinary Studies, 2023)
Learning Islamic religious education (PAI) in the school environment is one of the efforts of educational institutions to ward off intolerance and radicalism religious name. Through community-based sociocultural learning activities able to have a positive impact, namely creating a peaceful environment, tolerant and non-violent. This research uses a descriptive qualitative approach using interview, observation and documentation methods. PAI teacher served as the main informant in the research. The data analysis process was carried out simultaneously with the data collection process after data collection is complete. The research results show that (1) the concept of PAI learning through sociocultural is the link between religion and culture as a medium for learning topic of administering corpses in the community (2) steps PAI learning includes preliminary activities, core activities where the teacher convey religious knowledge using inquiry learning strategies and problem based learning, and finally the closing activity where the teacher and students reflect on learning results and draw conclusions from the material organizing the care of corpses (3) implications of PAI learning to reap results positive towards strengthening students' religious moderation which is reflected in life daily. The implications of PAI learning in strengthening religious moderation have an impact positive on students and the institution. This can be seen from the achievement of moderation indicators religion includes, fairness, mutual respect, mutual respect, ownership commitment to nation and nation, tolerance and love of peace.